The Health State of Patients with Diabetes During the COVID-19 Transition Period - Sulistini, Rumentalia; Mediarti, Devi; Sitorus, Nikson; Rosnani, Rosnani (JOSING: Journal of Nursing and Health, 2022)
This study aims to identify the health status of diabetic patients and related factors related to the COVID-19 transition period. This study used a cross-sectional design. Statistical tests showed a significant relationship between the length of illness (p= 0.003) and body mass index (p= 0.026) with health status scores. Vaccination history and other characteristics have no relationship with the patient's health. However, length of illness, body mass index, age, and level of education can significantly predict the patient's health. Measures of condition, body mass index, age, and level of education can be used to indicate a patient's state of health, with the duration of illness having a more significant effect. In conclusion, the health state during the transition from pandemic to endemic, according to the perception of people with diabetes mellitus, was good, the vaccination program must be continued, and community support, especially for cadres, is practical to improve the management of diabetics. Keywords: Health status, Diabetes Mellitus, Vaccination